Influence of Whole-Body Cryostimulation (–120°C) on Transformation of Blood Erythrocytes in Young Rats - Lomako, Victoria V.; Shylo, Oleksandr V.; Kovalenko, Igor F. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(3): 266–270